Tax Justice and Voluntary Compliance of the Taxpayers in Nigeria - Oyeniyi Oluwafunmilayo Caroline; Okoughenu Sunday Azeita (MultiTech Publisher, 2021)
The study examined how tax justice could influence voluntary tax compliance among taxpayers in Nigeria in which the theoretical underpinning was expediency theory which establishes the practicability and feasibility of a tax administration to the extent of its formulation and collection. The work’s methodology was an ex-post facto research design where the authors were afforded an avalanche of secondary sources-oriented data between 1981 to 2020. The proxies of Tax justice were Petroleum Profit Tax (PPT), Companies Income Tax (CIT), Duties and (D) while the proxies of voluntary compliance before the advent of Voluntary Assets Income and Declaration Scheme (VAIDS) is the Gross Domestic Product (GDP) upon which tax was paid). The result of the study of the main objective posited a significant relationship between tax justice and voluntary tax compliance among taxpayers (0.03 @ 5% significance level). The result of the specific objectives also revealed a significant relationship between the explained and explanatory variables (0.02, 0.00 @ 5% significant level). In addition, the Analysis of Variance (ANOVA) result of 0.00 is significant at the 5% level. Also, Pearson’s result shows a positive correlation between GDP on one hand and PPT, CIT, and D on the other hand. The study, therefore, concluded that with a virile and formidable tax justice system many taxpayers will voluntary and promptly file returns to pay tax since they can now feel the impact of the tax regime